Measuring Ownership, Control, and Use of Assets - Doss, Cheryl (World Bank, Washington, DC, 2017)
Assets generate and help diversify income, provide collateral to access credit, alleviate liquidity constraints in the face of shocks, and are key inputs into empowerment. Despite the importance of individual-level data on asset ownership and control, and that most assets are owned by individuals, solely or jointly, it is typical for the micro data on asset ownership to be collected at the household level, often from only one respondent per household. Even when the data are collected at the individual level, with identification of reported or documented owners of a given asset within the household, the information is still often solicited from a single respondent. Further, the identification of owners is seldom paired with the identification of individuals who hold various rights to assets, limiting understanding of the interrelationships among ownership and rights, and whether these relationships vary across individuals. Through a review of the existing approaches to data collection and the relevant literature on survey methodology, this paper presents an overview of the current best practices for collecting individual-level data on the ownership and control of assets in household and farm surveys. The paper provides recommendations in three areas: (1) respondent selection; (2) definition and measurement of assess to and ownership and control of assets; and (3) measurement of the quantity, value, and quality of assets. Open methodological questions that can be answered through analysis of existing data or the collection and analysis of new data are identified for future research.